Nitric Oxide Generated by Tumor-Associated Macrophages Is Responsible for Cancer Resistance to Cisplatin and Correlated With Syntaxin 4 and Acid Sphingomyelinase Inhibition - Perrotta, Cristiana; Cervia, Davide; Di Renzo, Ilaria; Moscheni, Claudia; Bassi, Maria Teresa; Campana, Lara; Martelli, Cristina; Catalani, Elisabetta; Giovarelli, Matteo; Zecchini, Silvia; Coazzoli, Marco; Capobianco, Annalisa; et al. (Frontiers in Immunology, 2018)
Tumor microenvironment is fundamental for cancer progression and chemoresistance. Among stromal cells tumor-associated macrophages (TAMs) represent the largest population of infiltrating inflammatory cells in malignant tumors, promoting their growth, invasion, and immune evasion. M2-polarized TAMs are endowed with the nitric oxide (NO)-generating enzyme inducible nitric oxide synthase (iNOS). NO has divergent effects on tumors, since it can either stimulate tumor cells growth or promote their death depending on the source of it; likewise the role of iNOS in cancer differs depending on the cell type. The role of NO generated by TAMs has not been investigated. Using different tumor models in vitro and in vivo we found that NO generated by iNOS of M2-polarized TAMs is able to protect tumor cells from apoptosis induced by the chemotherapeutic agent cisplatin (CDDP). Here, we demonstrate that the protective effect of NO depends on the inhibition of acid sphingomyelinase (A-SMase), which is activated by CDDP in a pathway involving the death receptor CD95. Mechanistic insights indicate that NO actions occur via generation of cyclic GMP and activation of protein kinase G (PKG), inducing phosphorylation of syntaxin 4 (synt4), a SNARE protein responsible for A-SMase trafficking and activation. Noteworthy, phosphorylation of synt4 at serine 78 by PKG is responsible for the proteasome-dependent degradation of synt4, which limits the CDDP-induced exposure of A-SMase to the plasma membrane of tumor cells. This inhibits the cytotoxic mechanism of CDDP reducing A-SMase-triggered apoptosis. This is the first demonstration that endogenous NO system is a key mechanism through which TAMs protect tumor cells from chemotherapeutic drug-induced apoptosis. The identification of the pathway responsible for A-SMase activity downregulation in tumors leading to chemoresistance warrants further investigations as a means to identify new anti-cancer molecules capable of specifically inhibiting synt4 degradation.